Effect of change in pH, heat treatment and diafiltration on properties of medium protein buffalo milk protein concentrate - Patil, Ashwajit Tejram (J Food Sci Technol, 2019)
The demand of milk protein concentrate (MPC) powders is continuously increasing as high protein dairy ingredients. Presence of higher calcium and casein contents; heating, ultrafiltration (UF), diafiltration (DF) and spray drying of buffalo skim milk induces undesirable changes in milk proteins that causes problem of poor solubility in MPC powders. Therefore, this investigation was aimed to study the effect of change in pH (6.8-native, 7.0-neutral), heat treatments (74 ± 1 °C/15 s, 80 ± 1 °C/5 min, 85 ± 1 °C/5 min, 90 ± 1 °C/5 min) and DF on physicochemical, functional, reconstitution and rheological properties of medium protein buffalo milk protein concentrate (MP-BMPC) powder. Based on maximum ζ-potential and heat stability, UF retentate was selected, diafiltered and spray dried to obtain MP-BMPC powder. Despite having higher protein content, MP-BMPC powder exhibited markedly better functional (solubility, wettability, viscosity and emulsion stability) properties than buffalo milk protein concentrate 60. The interstitial air content, occluded air content, loose bulk density, packed bulk density, particle density and porosity values of MP-BMPC powder were 145.97 and 112.92 mL 100 g(−1) of powder, 0.21 g mL(−1), 0.30 g mL(−1), 0.55 g mL(−1) and 65.09%. Further, its specific surface area; particle size distribution (d(10), d(50), d(90)); Sauter (D(32)) and DeBroukere (D(43)) mean values were 97.93 m(2) kg(−1); 34.32, 104.42, 218.58 µm; 61.27 µm and 117.99 µm. The storage modulus (G′) and loss modulus (G″) crossover temperature of UF and DF retentates were ~ 57.16 °C and 55.10 °C, respectively. Rheological behaviour of UF, DF retentates and MP-BMPC solution were best explained by Herschel-Bulkley model. Fourier-transform infrared spectroscopy best described amide I, II and III regions in 1700–1400 cm(−1) and 1350–1200 cm(−1) wavenumber range.